The Face of Yahweh? - Garfinḳel, Yosef (Biblical archaeology review, 2020)
The article offers information on male figurine heads that were excavated from the sites of Khirbet Qeiyafa and Mozạ located in the Kingdom of Judah. Topics include examines that five objects create a new type of male figurine, with three of them seeming to represent a rider on a horse; and focuses on combination of archaeological contexts, time periods, geographic distribution, iconography, Ugaritic texts, and the biblical tradition indicates that these figurines represent a male god.